Closed reduction and proximal femoral nailing in the management of intertrochanteric fractures: a prospective study - ., Santosha (International Journal of Research in Orthopaedics, 2018)
Background: Open reduction and dynamic hip screw with plate was considered as the standard method of treatment for intertrochantric fracture of femur previously. With the introduction of proximal femoral nails, closed reduction and proximal femoral nailing are used extensively for the treatment of intertrochantric fractures in the last two decades. The purpose of this study was to evaluate the functional outcome in early treatment of intertrochanteric fractures of Femur by closed reduction and proximal femoral nailing. Methods: Study was conducted in the department of orthopaedics in Regional Institute of Medical Sciences (RIMS), Imphal, Manipur, from August 2014 to August 2016. Forty cases of intertrochantric fractures are treated with proximal femoral nails. Patients were followed up for a period of 24 weeks. The modified Harris hip score (MMHS) was used to evaluate the functional outcome of surgery. Results: Forty consecutive patients were included in this study. Fractures were classified according to Boyd and Griffin classification system. According to the classification 16 cases were type I, 14 cases were type II, 5 were type III and 5 were of type IV. After 12 months of follow-up, all 40 patients were available for evaluation. Radiological union was achieved in a mean time of 14.5 weeks. MHHS was excellent in 13 patients good in 16 patients, fair in 8 patients and poor in 3 patients. Conclusions: Proximal femoral nailing systems are minimally invasive techniques with shorter operative time and good union rate.